DRUG-INDUCED REACTIONS IN STOMATOLOGY - Cristina-Maria Gavrilescu; Paloma Manea; Dragoş Munteanu; Rodica Ghiuru; Anca Janeta Stan; Christina Pascaru Isabelle; Cătălina Covalea; Crânguţa Paraschiv (Romanian Society of Oral Rehabilitation, 2015)
The huge importance of adverse reactions to drugs for public health is well proven. Any drug can produce side effects, and any of these reactions can have an oral manifestation. We have organized a pharmacoepidemiologic study to describe the drug-induced reactions manifested in the oral cavity in hospitalized patients (admitted in the Vth Internal Medicine Clinic) and in outpatients (consulted and treated in dental offices). For assessing side effects, the Adverse Drug Reaction Probability Scale was applied. 67 drug-induced oral reactions were described in the studied patients. The frequency was higher in women, in the elderly and in case of polypragmasia. The drugs most frequent incriminated in oral adverse reactions have been NSAIDs, antihypertensives, statins, antibiotics, corticoids and antidepressants. The most frequent reactions have been oral allergic reactions, xerostomia, stomatitis and abnormalities of taste. The best way of preventing and detecting oral side-effects is a team made up by dentists and doctors of different specialties.